Conformational dynamics of a G protein-coupled receptor helix 8 in lipid membranes - Dijkman, P; Munoz-Garcia, J; Lavington, S; Kumagai, P; dos Reis, R; Yin, D; Stansfeld, P; Costa Filho, A; Watts, A (American Association for the Advancement of Science, 2020)
G protein–coupled receptors (GPCRs) are the largest and pharmaceutically most important class of membrane proteins encoded in the human genome, characterized by a seven-transmembrane helix architecture and a C-terminal amphipathic helix 8 (H8). In a minority of GPCR structures solved to date, H8 either is absent or adopts an unusual conformation. The controversial existence of H8 of the class A GPCR neurotensin receptor 1 (NTS1) has been examined here for the nonthermostabilized receptor in a functionally supporting membrane environment using electron paramagnetic resonance, molecular dynamics simulations, and circular dichroism. Lipid-protein interactions with phosphatidylserine and phosphatidylethanolamine lipids, in particular, stabilize the residues 374 to 390 of NTS1 into forming a helix. Furthermore, introduction of a helix-breaking proline residue in H8 elicited an increase in ß-arrestin–NTS1 interactions observed in pull-down assays, suggesting that the structure and/or dynamics of H8 might play an important role in GPCR signaling.